Dispelling the manufacturing myth : American factories can compete in the global marketplace (National Academy Press, 1992)
An examination of manufacturing costs in domestic and offshore factories to provide insight into the factory location and decision making process.
Keywords: Manufacturing industries -- United States.; Competition, International.; Concurrence internationale.; BUSINESS & ECONOMICS -- Industries -- General.; Competition, International; Manufacturing industries; United States; Verarbeitende Industrie; Internationale Wettbewerbsfähigkeit; USA; plant location; -- factory site selection; -- global competition